2022
DOI: 10.1097/mnm.0000000000001638
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT parameters for prediction of response to neoadjuvant therapy and prognosis in rectal cancer

Abstract: Objective This study aims to investigate the role of F-18 fluorodeoxyglucose PET/computed tomography (18F-FDG PET/CT) parameters in the prediction of treatment response and the prognosis in locally advanced rectal cancer. Methods We investigated the relationship of 18F-FDG PET/CT parameters [rectal metabolic tumor volume (MTV), rectal total lesion glycolysis (TLG), rectal standard uptake value (SUV) max, rectal highest peak SUV, lymph node MTV, lymph node TLG, lymph node highest peak SUV] with the pathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…4 ). The prognostic value of MTV has been extensively investigated in various malignancies; patients with higher MTV tend to have a poorer prognosis [ 23 25 ]. Similarly, in our study, we also found that MTV was associated with the clinical benefit of immunotherapy in NSCLC patients, and this finding was consistent with previous studies that had similar results [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 ). The prognostic value of MTV has been extensively investigated in various malignancies; patients with higher MTV tend to have a poorer prognosis [ 23 25 ]. Similarly, in our study, we also found that MTV was associated with the clinical benefit of immunotherapy in NSCLC patients, and this finding was consistent with previous studies that had similar results [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%